Adaptive Multimedia Retrieval: Retrieval, User, and Semantics 5th International Workshop, AMR 2007, Paris, France, July 5-6, 2007, Revised Selected Papers - Boujemaa, Nozha; Detyniecki, Marcin; Nürnberger, Andreas (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2008)
This book constitutes the thoroughly refereed post-workshop proceedings of the 5th International Workshop on Adaptive Multimedia Retrieval, AMR 2007, held in Paris, France, in July 2007. The 18 revised full papers presented together with 2 invited papers were carefully selected during two rounds of reviewing and improvement. The papers are organized in topical sections on image annotation, feedback and user modelling, music retrieval, fusion, P2P and middleware, databases and summarization, as well as ontology and semantics.